2020
DOI: 10.21082/jpasca.v15n3.2018.155-163
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Dan Potensi Penggunaan Iridiator Merah Putih Untuk Penanganan Produk Pangan Hasil Pertanian

Abstract: <p>Iradiator gamma, yang diberi nama iriradiator Merah Putih, telah selesai dibangun dan diisi dengan sumber Cobalt-60 dengan kapasitas sekitar 300 kCi. Dirancang untuk multiguna, iriadiator ini harus dapat menyediakan berbagai dosis serap dari rendah hingga tinggi. Sistem kontrol mengijinkan 4 opsi kombinasi rak-rak sumber dengan opsi aktivitas terkceil adalah 41,2 kCi. Di dalam bungker, produk akan menjalani mekanisme laluan iradiasi dengan tujuan agar mendapatkan dosis serap iradiasi yang beragam. Bun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Bone breadfruit flour has a softer texture compared to other varieties. The amylose content of this study was higher than that of [16], who reported that breadfruit flour has amylose content ranging from 11.8 to 20.70%. The dietary fiber of breadfruit flour in this experiment is significantly different between varieties, that ranged from 6.85-8.11%.…”
Section: Chemical Propertiescontrasting
confidence: 77%
“…Bone breadfruit flour has a softer texture compared to other varieties. The amylose content of this study was higher than that of [16], who reported that breadfruit flour has amylose content ranging from 11.8 to 20.70%. The dietary fiber of breadfruit flour in this experiment is significantly different between varieties, that ranged from 6.85-8.11%.…”
Section: Chemical Propertiescontrasting
confidence: 77%